2016
DOI: 10.1016/j.concog.2016.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Imagining the future: A cross-cultural perspective on possible selves

Abstract: This study examined the impact of culture on the qualitative and quantitative features of possible selves. Young adults from Turkey (n = 55), Serbia (n = 64), and the United Kingdom (n = 73) generated images of eight possible selves (e.g. I will be a doctor) which were dated and rated for vividness, positivity, imagery perspective, rehearsal, and according to whether or not they involved other people. All possible selves were coded according to categories (e.g. job, parenthood, self-improvement). There were cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 47 publications
1
20
0
Order By: Relevance
“…specific self-images) generated for distant versus near future self-images when they were explicitly manipulated. Rathbone et al (2016) explained that, although this appears counter to construal-level theory (Trope & Liberman, 2010), it can be explained by distant self-images mapping on to cultural life scripts; replicated herein. Additionally, it is possible that when thinking of the near future, participants draw upon already present aspects of self, such as ubiquitous attributes (e.g., being caring, which can be present across multiple aspects of self; see Donahue et al, 1993;McConnell, 2010).…”
Section: The Content Of Self-imagesmentioning
confidence: 59%
See 2 more Smart Citations
“…specific self-images) generated for distant versus near future self-images when they were explicitly manipulated. Rathbone et al (2016) explained that, although this appears counter to construal-level theory (Trope & Liberman, 2010), it can be explained by distant self-images mapping on to cultural life scripts; replicated herein. Additionally, it is possible that when thinking of the near future, participants draw upon already present aspects of self, such as ubiquitous attributes (e.g., being caring, which can be present across multiple aspects of self; see Donahue et al, 1993;McConnell, 2010).…”
Section: The Content Of Self-imagesmentioning
confidence: 59%
“…In a recent study, Rathbone et al (2016) demonstrated that specific (versus abstract) possible self-images were dated as emerging in the more distant (versus near) future. Our results are consistent with this, in that we found fewer attributes (cf.…”
Section: The Content Of Self-imagesmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to research on episodic future thinking, research on future self-images has also demonstrated that when people are asked to freely generate future self-images, they usually produce a higher proportion of positive than negative self-images (Rathbone, Conway, & Moulin, 2011;Rathbone, Salgado, Akan, Havelka, & Berntsen, 2016). In addition, there is evidence suggesting that this bias favoring the generation of positive self-images is found across young, middle-age and older adults (Salgado & Berntsen, 2018), and that positive self-images are dated to emerge closer to the person's present regardless of age (Chessell, Rathbone, Souchay, Charlesworth, & Moulin, 2014;Smith & Freund, 2002).…”
Section: Self-imagesmentioning
confidence: 92%
“…After all, they might share the intuitions of social psychologists [80] more than those of philosophers, who put less emphasis on social roles. When imagining possible future selves, participants from different cultures focused not only on abstract self-improvement, but also on future social relations [84]. Considering the continuity of social relations as a criterion for personal identity led us to the following prediction:…”
Section: Research Questions and Hypothesesmentioning
confidence: 99%